Effects of Laser Energy on n-Ge/p-SnS Hetrojunction Diode Detector in Different Environments - Abduljabbar, Laith M. (Iraqi Journal of Laser, 2019)
In the present work, heterojunction diode detectors will be prepared using germanium wafers as a substrate material and 200 nm tin sulfide thickness will be evaporated by using thermal evaporation method as thin film on the substrate. Nd:YAG laser (λ=532 nm) with different energy densities (5.66 J/cm2 and 11.32 J/cm2) is used to diffuse the SnS inside the surface of the germanium samples with 10 laser shots in different environments (vacuum and distilled water). I-V characteristics in the dark illumination, C-V characteristics, transmission measurements, spectral responsivity and quantum efficiency were investigated at 300K. The C-V measurements have shown that the heterojunction were of abrupt type and the maximum value of build-in potential is equal to 1.78V in water environment .The results showed that the detectors have two peaks at 900 nm and 1250 nm and the maximum spectral responsivity can be obtained at λ=1250 nm in water environment. Also the quantum efficiency has two peaks at 900nm and 1250 nm and it is increase the increase in laser energy density and this increase is to be clear in the water environment more than the vacuum environment.